The Improvement of Result Learning Mathematic Through Peer Teaching Method on The Factorization Algebra Material of The Students VIII-3 Class at SMP Negeri 5 Parepare - Arifin Arifin; Hastuty Musa; Samsir Alam (MEJ (Mathematics Education Journal), 2018)
The research is a class action (Classroom Action Research). The aim of this research is to determine whether learning result can improve through learning mathematics Peer Teaching Method of factorization algebra material of students in class VIII3 at SMP Negeri 5 Parepare. The method of the researcher was Peer Teaching Method (a teaching method their peers in small groups). The subject of research is the students of VIII3 class at SMP Negeri 5 Parepare that is consisted of 18 students. The implementation of this research consisted of two cycles in each cycle consisting of four stages, such as: (a) planning stage, (b) action stage, (c), observation stage, (d) reflection stage. The collecting data analyzed by quantitative and qualitative analysis. The conclusion is the result of mathematic learning can improve through peer teaching method of the students VIII3 class at SMP NEGERI 5 PAREPARE.